2008
DOI: 10.3197/096734008x333572
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Traditional Land Use in South-Central Sweden: The Significance of Management Timing

Abstract: During the last 50-100 years, large numbers of species associated with seminatural grassland have declined. One reason for this is the considerable reduction of grassland area. Another possible explanation is the loss of historical management practices. This study addresses changes in the timing of management and its implications for biodiversity, and combines historical data on management timing (eighteenth century) with data on reproductive phenology of vascular plants and butterflies. All data are from sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…Several of the management components lost from Swedish management affect plant populations directly. For example, traditional late mowing, later than the Swedish late-July mowing, is crucial for the seed production of many grassland plant species (Lennartsson et al 2012) and for the reproduction of phytophagous insects (Dahlström et al 2008). To our knowledge, this study is the most extensive (in terms of time span and number of monitored species) evaluation of how CAP-driven hay meadow management in Sweden affects biodiversity.…”
Section: Traditional Management Practices and Biodiversity In Swedenmentioning
confidence: 99%
“…Several of the management components lost from Swedish management affect plant populations directly. For example, traditional late mowing, later than the Swedish late-July mowing, is crucial for the seed production of many grassland plant species (Lennartsson et al 2012) and for the reproduction of phytophagous insects (Dahlström et al 2008). To our knowledge, this study is the most extensive (in terms of time span and number of monitored species) evaluation of how CAP-driven hay meadow management in Sweden affects biodiversity.…”
Section: Traditional Management Practices and Biodiversity In Swedenmentioning
confidence: 99%
“…An early onset of grazing (April, May) and which continues throughout the season restricts flowering and seed production of vascular plants (Brys et al, 2004;Lennartsson & Oostermeijer, 2001). The seeds of the majority of grassland plant species ripen between late July to mid August (Dahlström et al, 2008;Wissman, 2006). Even small adjustments of the timing of disturbance within this time window will have large effects on seed production (cf.…”
Section: Ecological Significance Of Timing Of Disturbancementioning
confidence: 99%
“…Arrhenius & Lindquist, 1904;Ohlsson, 2006). Hay meadows were historically mown during a certain mowing period, often c. one month of length and starting in late June to mid July (Dahlström et al, 2008;Vestbö-Franzén, 2004, pp. 171-172).…”
Section: Management Components Affecting Timing Of Disturbancementioning
confidence: 99%
See 1 more Smart Citation
“…1). Dahlström et al (2008) show that the highest species richness in plants in central sweden is found in what today is semi-natural grassland subjected to a long continuity of grazing. It is estimated that since 1870, 99.7% of the semi-natural hay meadows have been lost, the few remaining semi-natural hay meadows are now managed mainly for conservation purposes.…”
Section: Science Highlights: Sustaining Earth's Biodiversitymentioning
confidence: 99%